Economic Monitoring Report to the Ad Hoc Liaison Committee - World Bank Group (World Bank, Washington, DC, 2020)
The report reviews recent economic developments in the real, fiscal and banking sectors, while providing a near-term outlook that highlights critical challenges facing the Palestinian economy. Additionally, it looks at the opportunities and constraints facing digital infrastructure in the Palestinian territories, the development of which is critical to the future expansion of the digital economy. It makes short- and long-term recommendations that would allow more digital activity and job creation. This report assesses the status of the World Bank recommendations to the Ad Hoc Liaison Committee meeting over the years and identifies recent legal and regulatory advancements by the Palestinian Authority in the telecommunications sector.